How to use a controlled fast to investigate hypoglycaemia. Issue 1 (24th August 2016) - Sreekantam, S; Preece, M A; Vijay, S; Raiman, J; Santra, S
Abstract : Controlled fasts can play a valuable role in the diagnosis and management of hypoglycaemia in paediatric clinical practice, but are no substitute for the collecting of appropriate critical samples at the time of hypoglycaemia for metabolic and endocrine studies. Fatty acid oxidation defects, hyperinsulinism and adrenal insufficiency should always be excluded prior to organising controlled fasts. Controlled fasts are safe if conducted in an experienced setting with strict protocols in place. Failure to adhere to protocol can defeat the purpose of the study and can potentially be dangerous. Proper planning in conjunction with the laboratory and close supervision by staff experienced in controlled fasts is crucial to ensure the best quality information is yielded from these procedures.